COMPARITIVE STUDY OF ESBL MEDIATED DRUG RESISTANCE AMONG CLINICAL AND COMMUNITY ISOLATES OF ESCHERICHIA COLI - DR.V.NAGAMADHAVI; DR.V.C.BHARATHI; DR.SUBADRADEVI (International Journal of Pharma and Bio Sciences, 2013)
The emergence and spread of resistance to antibiotics among common pathogenic bacteria is an important health care concern. Today the magnitude of the problem has become a threat to reverse the scientific progress made so far. The aim of the study is to identify various strains of Escherichia coli isolated from hospital and community infections, to study their production of ESBL, and their antibiogram so as to guide the clinician to plan proper antibiotic policy, thereby reducing the mortality and morbidity due to bacterial infections. Antibiotic sensitivity test is done by using Kirby– Bauer’s method of disc diffusion susceptibility test and it is confirmed by Double disc synergy test, Phenotypic confirmatory disc diffusion test. : Among 100 isolates of Escherichia coli 25 isolates from hospital, 8 isolates from community are resistant to 3rd generation cephalosporins. Among these, 12 isolates from hospital, and 4 isolates from community are ESBL producers. The present study highlights that there is a significant difference in drug resistance pattern between hospital to community strains.